PENERAPAN ACTION CONTROL UNTUK MENINGKATKAN KUALITAS LAYANAN PENGAJARAN PADA BRI CORPORATE UNIVERSITY CAMPUS SURABAYA - Raihan Bari Muhammad; Ria Sandra Alimbudiono (Perpustakaan Universitas Surabaya, 2018)
In today's modern era, competition among banking institutions is getting tighter. Almost everyone has taken advantage of banking services in transactions, whether in storage transactions, loans, or other financial transactions. Competition among banking institutions is increasingly stringent, requires every banking institution to pay more attention to the needs of consumers or customers. Good service is the only key to winning the competition in the banking world. This good service can be realized through good employee performance. Good employee performance can be realized through various things, such as training, giving incentives, giving satisfaction to employees and etc. Business entities have several ways of controlling employee behavior, one of the ways that can be used is implementing management control system. One form of control system is action control, ie controls performed on processes, ways and actions by employees in performing their duties. The purpose of this study is to analyze the implementation of action control to improve quality of teaching service at BRI Corporate University Campus Surabaya. Action control and service quality is the most supportive overall. By being able to control the behavior of employees then employees will be able to act correctly is by applying the maximum quality of service.